2017
DOI: 10.1159/000482022
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Alcohol Consumption Effects on Blood Pressure and on Kidney Structure Persist After Long-Term Withdrawal

Abstract: Background/Aims: Heavy ethanol consumption is a risk factor for hypertension and prompts organ damage. There is no information regarding the impact of long-term heavy ethanol consumption on kidney structure and function linking to their hypertensive effects nor the repercussions after withdrawal. Methods: Rats were exposed to ethanol for 24 weeks and, afterwards, a group was assigned to withdrawal for 8 weeks. Blood pressure (BP) was measured and serum biochemical parameters were quantified. Glomerular volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
0
18
1
Order By: Relevance
“…As for the kidney damage caused by alcohol, some studies discovered that the patients’ renal function recovered after abstinence [1]. However, others also found that abstinence cannot completely repair the kidney injury [26]. Unfortunately, existing clinical studies have not analyzed why some patients with CKD give up drinking and the influence of giving up drinking on the prognosis of these patients.…”
Section: Special Benefits and Confounding Factors Of Alcohol Consumptionmentioning
confidence: 99%
“…As for the kidney damage caused by alcohol, some studies discovered that the patients’ renal function recovered after abstinence [1]. However, others also found that abstinence cannot completely repair the kidney injury [26]. Unfortunately, existing clinical studies have not analyzed why some patients with CKD give up drinking and the influence of giving up drinking on the prognosis of these patients.…”
Section: Special Benefits and Confounding Factors Of Alcohol Consumptionmentioning
confidence: 99%
“…Leal et al found that heavy alcohol consumption led to renal atrophy in rats. The finding was not reversible even after long-term withdrawal [21]. Any cause of renal disease may lead to hypertension.…”
Section: Secondary Hypertensionmentioning
confidence: 82%
“…The multiple mechanisms through which AUD may leave patients vulnerable to AKI include oxidative stress on the kidney, which metabolizes roughly 10% of consumed ethanol [35]. Alcohol induces production of free radicals [36][37][38][39][40] and also decreases antioxidant capabilities of enzymes in the kidney [41][42][43]. In a recent comprehensive review on clinical studies looking at links between CKD and alcohol consumption, Fan et al (2019) concluded that light-to moderate drinking may not have adverse effects on patients with CKD [44].…”
Section: Discussionmentioning
confidence: 99%